Сomparative analysis of the accounting systems of Ukraine and China - Ding, Junpeng (Харківський національний автомобільно-дорожній університет, 2024)
A number of definitions are highlighted and a comparison of approaches to definitions of the essence of the accounting system is carried out, the definitions are studied for their shortcomings, and their own vision of the definition of "accounting system" is proposed. The types of influence of micro- and macroenvironmental factors on the accounting system are clarified, a number of features of accounting systems are outlined, general concepts of classifications of accounting systems are studied, and the principles of the modern accounting system in Ukraine are outlined. The system of regulatory and legal regulation of the accounting system in Ukraine and China is highlighted, and their main aspects are analyzed. The existing accounting systems in the world are outlined and their characteristics are studied; similarities and differences between the accounting systems of Ukraine and China are clarified, their advantages and disadvantages are assessed.
Keywords: accounting system; financial reporting; accounting; concepts; principles; national regulations; international financial reporting standards